Application of Duplitecture to Public Spaces in The City Center Case Study: Umbrella Madinah Pasuruan City - Sunarya, Wendy; Imtyaas, Yasmine Jauzaa; Dilla, Adinda Salsa; Utomo, Heru Prasetiyo; Harmunisa, Yusvika Ratri (Universitas Muhammadiyah Surakarta, 2025)
Duplitecture has become a captivating trend in Indonesia tourism. Duplitecture refers to the imitation or duplication of a popular architectural object that is intentionally built in a different place to enhance the tourist attraction within an area. Duplitecture usually adopts iconic architectural objects from foreign countries or those already globally famous. The trend of duplitecture invites debate because on one hand, it can be seen as plagiarism, but it can also be appreciated for its tourist appeal. This study examines the implementation of duplitecture in public spaces in downtown areas with a case study of Payung Madinah in Pasuruan City, East Java, mimicking the design of the Umbrellas of Al-Masjid An-Nabawi in Medina, Saudi Arabia. The aim is to investigate the important influences that limit or encourage the development of the duplitecture trend. Literature review was conducted in this research to discuss the duplitecture trend from various perspectives. Qualitative methods through field observation and interview were also applied to see the impact of the object existence. The study results show that the Payung Madinah in Pasuruan City has successfully become a positively impactful duplitecture object appreciated by the community. In addition to its unique shape, the object can provide functional space and offer new experiences to visitors in the downtown area. Its presence is strengthened by the religious tourism area around it, thus creating mutually beneficial benefits for the community, the image of the area, and its own existence.